Critical Thinking in AI-Assisted EFL Learning: A Systematic Literature Review - Sylvia (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
The rapid advancement of Artificial Intelligence (AI) has transformed educational practices and created new opportunities for fostering critical thinking in English as a Foreign Language (EFL) learning. As critical thinking is increasingly recognized as a key competency in twenty-first-century education, understanding the role of AI in supporting higher-order thinking skills has become an important area of research. However, existing studies remain fragmented across different educational contexts, language skills, and AI applications. Therefore, this study aimed to systematically review recent empirical research on the role of AI in fostering critical thinking in EFL learning. This study employed a qualitative Systematic Literature Review (SLR) design. Relevant studies were collected from major academic databases, including Google Scholar, Scopus-indexed journals, ScienceDirect, Taylor & Francis, SpringerLink, Wiley Online Library, and ERIC. Following predetermined inclusion and exclusion criteria, six peer-reviewed studies published between 2024 and 2026 were selected and analyzed using qualitative content analysis. The analysis focused on four themes: geographical distribution of studies, language skills investigated, critical thinking dimensions addressed, and the roles of AI in fostering critical thinking. The findings revealed that research on AI-assisted critical thinking is concentrated primarily in China, Oman, and Türkiye, with writing and reading being the most frequently investigated language skills. The studies demonstrated that AI supports various dimensions of critical thinking, particularly analysis, evaluation, inference, interpretation, and self-regulation. Furthermore, AI functions as a writing assistant, cognitive and dialogic partner, feedback provider, and pedagogical scaffold. However, critical thinking development depends not merely on AI accessibility but on ethical, reflective, and pedagogically guided implementation. The review concludes that AI has substantial potential to enhance critical thinking in EFL learning when supported by structured scaffolding, metacognitive guidance, and meaningful learner engagement.